Comprehensive and critical appraisal of plant-based defluoridation from environmental matrices. (October 2021) - Sharma, Ritika; Sharma, Rozi; Parveen, Khalida; Pant, Deepak; Malaviya, Piyush
Abstract: Fluoride is recognized as one of the global environmental threats because of its non-biodegradable nature and long-term persistence in the environment. This has created the dire need to explore various defluoridation techniques (membrane process, adsorption, precipitation, reverse osmosis, ion exchange, and electrocoagulation). Owing to their cost ineffectiveness and high operational costs, these technologies failed to find any practical utility in fluoride remediation. Comparatively, defluoridation techniques involving the use of low-cost plant-derived adsorbents and fluoride phytoremediators are considered better alternatives. Through this review, an attempt has been made to critically synthesize information about various plant-based bioadsorbents and hyperaccumulators from existing literature. Moreover, mechanisms underlying the fluoride adsorption and accumulation by plants have been thoroughly discussed that will invigorate the researchers to develop novel ideas about process/product modifications to further enhance the removal potential of the adsorbents and plants. Literature survey unravels that various low-cost plant-derived adsorbents have shown their efficacy in defluoridation, yet there is an urgent need to explore their pragmatic application on a commercial scale. Highlights: State of the art presented on the use of various bioadsorbents and plants in defluoridation. Effect of parameters such as pH, temperature and kinetics is discussed. Overview of F − adsorption mechanisms, thermodynamic studies and uptake mechanisms. Exploration and selection of low-cost adsorbents and phytoremediators is required. Necessity of modification and commercialisation of specific adsorbents and plants highlighted. Abstract : The review synthesizes and critically evaluates various low-cost plant-based adsorbents and fluoride hyperaccumulators that can be utilized in the defluoridation of contaminated environmental matrices. Reuse and practical application of agricultural wastes, peels of fruits, shells, husk, tea residues, etc as potential adsorbents aims to eradicate waste, ultimately providing benefit to the environment as well as raising the economy of the country.